PERAN PSIKOLOGI DALAM INVESTIGASI KASUS TINDAK PIDANA - Yusti Probowati R., DR. (Indonesian Journal of Legal and Forensic Sciences (IJLFS); Vol 1 (2008): Indonesian Journal of Legal and Forensic Sciences, 2008)
One of the problems in criminal/prime court is the truth of testimony. Most testimonies given may bebiased. This is caused by the vulnerabilities of human memory and the mistakes in digging deep through thewitness’ information. This paper aims to explain these problems from the perspective of psychologicalforensics, describing why human memory is so vulnerable, and which techniques of investigation interviewscan be best used for handling the problems.
Keywords: criminal/prime court, perspective of psychological forensics